Association of polymorphisms in gastric cancer in latin american individuals: A brief systematic review (Revista Contexto & Saúde, 2026)
Objective: To systematically compile all information that clarifies which genetic polymorphisms are associated with gastric cancer in South American individuals. Methods: A systematic review was conducted following the PRISMA model and PICO strategy, based on the guiding question: “Which genetic polymorphisms are related to gastric cancer in the Latin American population?” Articles were searched in the PubMed, LILACS, BVS, and Google Scholar databases, following defined inclusion and exclusion criteria. Fifty-two articles were found, and after analysis, 12 were definitively included in the review. Results: Several polymorphisms were identified in various genes involved in gene regulation, protein coding, inflammatory processes, oncological malnutrition, and drug-gene interaction, acting as potential molecular markers for the development of gastric cancer. Conclusion: The discovery of possible biomarkers that guide the relationship between gastric cancer and the polymorphisms of the genes studied in this review is promising. However, further studies are needed to better investigate this relationship and clarify the development of this pathology based on variations in various genes, allowing for future diagnostic approaches based on Single Nucleotide Polymorphism and genetic intervention in gastric cancer.